Newest and most promising Type 1 Diabetes treatment - Umm E Salma Banatwala,; Rayaan Imran,; Muhammad Usman Taufiq, (Journal of the Pakistan Medical Association, 2023)
Dear Madam, According to the International Diabetes Federation, Pakistan has the highest diabetes prevalence in the world (1).Ttype 1 diabetes (T1DM), a chronic condition where the pancreas makes little or no insulin. Despite extensive research, cure for T1DM has not been found. Typical treatment uses insulin injections, diet modifications, and exercise to manage blood sugar. This letter concisely explains the latest treatments for T1DM. Conventionally, exogenic insulin substitution was done by testing blood sugar levels after finger pricking. However, modern treatments include automated glucose monitoring technology and insulin pumps. Since T1DM is an autoimmune disease caused by the destruction of B-cells, the replacement of B-cells using allogeneic solid organ pancreas or islet transplantation treats the disease (2). However, this treatment requires lifelong immunosuppression drugs, that could lead to severe infections or nephrotoxicity. Other approaches include targeting T-cells, B-cells, or specific single antigens of which limitations range from side effects due to cytokine storm or inability to identify the key antigen. Even though immunotherapies further refined targeted inflammatory pathways, there is a lack of evidence as to if they can restore immune tolerance. On the other hand, therapies targeting cell-intrinsic metabolism may enhance B-cell survival but may result in B-cell dysfunction (2). Given the grim situation of current T1DM treatments, the artificial pancreas is revolutionary. Specific hybrid artificial pancreas required the patient to count the carbohydrates consumed at mealtime. The modern system uses continuous glucose monitoring technology (a sensor inserted under the skin), delivering insulin via the infusion pump according to the blood glucose level. The modern MiniMed 780G artificial pancreas is the first insulin delivery system to automatically administer bolus correction insulin dosage every 5 minutes and adjust insulin doses based on glucose levels. This technology can rectify insufficient or skipped pre-meal dosages by providing extra insulin. A study of 4120 780G users reported that outcomes matched the recommended goals by the American Diabetes Association’s Standards while commending its ability to achieve low variability in glycemic controls (3). Another prospective study published in 2023 concluded that switching to the 780G improves the restoration of hypoglycemia awareness and metabolic control(4). One notable side effect of this system is localized skin infection(5). In conclusion, treatment options for T1DM are ever-growing. The artificial pancreas shows promising results with milder side effects compared to other treatments. Further advancements are integral.